Effects of soy isoflavones on menopausal symptoms in perimenopausal women: a systematic review and meta-analysis - Haodi Luan; Qianqian Liu; Yahui Guo; Hua Fan; Sileng A.; Jing Lin (PeerJ, 2025)
Soy isoflavones are phytoestrogens found mainly in soy and its derivatives. Given their estrogen-like and antioxidant-inhibiting inflammatory effects, they have been hypothesized to be effective in treating menopausal symptoms. We conducted a systematic review in accordance with the PRISMA guidelines. In October 2024, we screened 2,099 articles, of which 12 were eligible for meta-analysis, and found that soy isoflavones were effective for treating menopausal symptoms (seven studies, 533 participants, Hedges’ g = −0.25, 95% CI [−0.42 to −0.08], p = 0.00). Soy isoflavones showed significant effects on headache (three studies, 340 participants, Hedges’ g = −0.38, 95% CI [−0.60 to −0.17], p = 0.00), psychosocial symptoms (five studies, 416 participants, Hedges’ g = −0.29, 95% CI [−0.48 to −0.10], p = 0.00), palpitation (three studies, 356 participants, Hedges’ g = −0.42, 95% CI [−0.63 to −0.22], p = 0.00), and depression (four studies, 748 participants, Hedges’ g = −0.72, 95% CI [−1.17 to −0.28], p = 0.00), but no significant treatment effect on paresthesia symptoms, fatigue symptoms, physical symptoms, hot flushes, excessive sweating, insomnia, and vasomotor symptoms was observed. However, our results should be interpreted with caution owing to the small sample size. More trials should be conducted in the future to validate our findings.